Novel N-Arylsulfonylindoles Targeted as Ligands of the 5-HT6 Receptor. Insights on the Influence of C-5 Substitution on Ligand Affinity - Loreto Arrieta-Rodríguez; Daniela Espinoza-Rosales; Gonzalo Vera; Young Hwa Cho; David Cabezas; David Vásquez-Velásquez; Jaime Mella-Raipán; Carlos F. Lagos; Gonzalo Recabarren-Gajardo (Pharmaceuticals, 2021)
A new series of twenty-two C-5 substituted N-arylsulfonylindoles was prepared with the aim of exploring the influence of C-5 substitution on 5-HT6 receptor affinity. Eleven compounds showed moderate to high affinity at the receptor (Ki = 58–403 nM), with compound 4d being identified as the most potent ligand. However, regarding C-5 substitution, both methoxy and fluorine were detrimental for receptor affinity compared to our previously published unsubstituted compounds. In order to shed light on these observations, we performed docking and molecular dynamics simulations with the most potent compounds of each series (4d and 4l) and PUC-10, a highly active ligand previously reported by our group. The comparison brings about deeper insight about the influence of the C-5 substitution on the binding mode of the ligands, suggesting that these replacements are detrimental to the affinity due to precluding a ligand from reaching deeper inside the binding site. Additionally, CoMFA/CoMSIA studies were performed to systematize the information of the main structural and physicochemical characteristics of the ligands, which are responsible for their biological activity. The CoMFA and CoMSIA models presented high values of q2 (0.653; 0.692) and r2 (0.879; 0.970), respectively. Although the biological activity of the ligands can be explained in terms of the steric and electronic properties, it depends mainly on the electronic nature.